Analisis Faktor yang Mempengaruhi Behavior Intention (Studi pada Wisatawan di Objek Wisata Puthuk Setumbu Borobudur) - Eny Endah Pujiastuti; Lukmono Hadi; Siti Aminatul Zahro (Jurnal Administrasi Bisnis, 2020)
Behavior intention is a key indicator that shows the success of tourism marketing strategies. The study is aimed to explain the effect of tourist experiences, satisfaction, trust, and behavior intention. Research location in the destination of Puthuk Setumbu, Borobudur. The research sample is the tourists who have visited Puthuk Setumbu Borobudur once, in Kurahan, Karangrejo Village, Borobudur District, Magelang Regency. The sample is the first time tourists because the research variable used is the intention to repurchase behavior. Data collected through a questionnaire. A total of 119 questionnaires were returned and data were analyzed using SEM AMOS. This research uses a relationship marketing approach. The results showed that there was a direct influence between tourist experience, satisfaction, trust and behavior intention.